The strategy of venue creation: Explaining health policy change in Greece - Maria Mavrikou; Nikolaos Zahariadis; Vassilis Karokis-Mavrikos (International Review of Public Policy)
How do policy entrepreneurs affect policy change in environments of institutional instability? The literature has predominantly explored policy entrepreneur strategizing in contexts with established institutional settings. In this paper, we argue that under conditions of institutional fluidity and a weak and politicized public administration, venue creation is the more frequently encountered and the more likely successful strategy. We define venue creation as the entrepreneurial strategy of setting-up institutional arrangements of finite duration, predominantly in the form of committees, delegated exclusively with designing reforms. We test our hypothesis in the Greek health policy sector. We explore two policy instances: the unsuccessful attempt at a public health reform in 1992 and the successful introduction of radical policy change for public health in 2003. We employ a process tracing approach spanning thirty years, processing primary data (elite interviews and documents) applying the Multiple Streams Framework (MSF). We find that under conditions of institutional fluidity and administrative weakness, policy entrepreneurs failed in their pursuit of change using venue shopping in 1992 but succeeded through venue creation in 2003, confirming our hypothesis. We conclude with insights for contingent policy entrepreneurship success, the MSF and patterns of policymaking in Greece.